Electrochemical and Electroless Deposition of High-Entropy Alloy Thin Films: A Review of Plating Conditions, Properties, and Applications - Ewa Rudnik (Applied Sciences, 2025)
High-entropy alloys (HEAs) represent a breakthrough class of materials characterized by a unique combination of properties derived from their multielement compositions. This review explores the current advancements in both electrochemical and electroless deposition techniques for synthesizing HEA thin films. This paper discusses the crucial plating conditions using aqueous or organic electrolytes and various current/potential modes that influence the formation, quality, and properties of these complex alloy coatings. Particular attention is given to their emerging applications in areas such as catalysis, protective coatings, microelectronics, and liquids’ separation. A comparison of electrochemical versus electroless methods reveals insights into the advantages and limitations of each technique for research and industrial use. This comprehensive review aims to guide further innovation in the development and application of HEA coatings.